EFEK LATIHAN “POWER PLYOMETRICS” DALAM SISTEM SET DAN SISTEM SIRKUIT TERHADAP PENINGKATAN DAYA LEDAK OTOTTUNGKAI - Ever Sovensi (JURNAL STAMINA, 2018)
Based on the author's observation in the field it was found that the ability of explosive limb muscles of volleyball players of SMAN 2 South Bengkulu was still low. The low ability of explosive limb muscle power is thought to be caused by the use of inappropriate training methods by the trainer in coaching. This study aims to reveal the effects of power plyometrics training in system sets and circuit systems on the ability of explosive limb muscle power of volleyball players of SMAN 2 South Bengkulu. This type of research belongs to the category of quasiexperimental research. The aim is to reveal the influence of two or more variables on other variables. The research design used was The One Group PretestPosttest Design. The population of this study was 22 male players, while the sample was determined by total sampling so that a sample of 22 male players was obtained. The test used is a vertical jump test which aims to determine the explosive ability of limb muscles of volleyball players of SMAN 2 South Bengkulu, while the data analysis used is the t-test. The results of data analysis showed that: (1) power plyometrics training using the set system significantly affected the increase in explosive muscle leg power of volleyball players at SMAN 2 Bengkulu Selatan ... (2) power plyometrics training using a circuit system had a significant effect on increasing limb muscle explosive power volleyball player at SMAN 2 South Bengkulu. (3) power plyometrics training using a set system gives a more effective influence than a circuit system to increase the explosive muscle power of a volleyball player in SMAN 2 South Bengkulu.